New Essays on the African American Novel
IX, 281 p.
Keywords: This collection contributes to scholarly discussions about the African American novel as a literary form. Essays respond to the general question, what has been the impact of the African American vernacular tradition from the spirituals, blues, gospel and jazz to hip hop on the structure and style of the modern African American novel?